1995
DOI: 10.1121/1.413465
|View full text |Cite
|
Sign up to set email alerts
|

Time and frequency domain characteristics of sperm whale clicks

Abstract: Regular clicks from diving sperm whales, both large bull males and smaller females, were recorded in deep oceanic water off the Azores and subsequently sampled to computer disks for digital analysis. A total of 8540 clicks were marked and analyzed. Simple temporal analysis of the interclick intervals during feeding dives revealed mean click rates for male sperm whales of 1.1713 s-1 and 1.9455 s-1 for females. Fourier analysis showed distinctive peaks in the spectra of bull male sperm whales at 400 Hz and 2 kHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 10 publications
(12 reference statements)
5
104
0
Order By: Relevance
“…Clicks during creaks have an initial inter-click interval of ca. 0.2 s, which decreases to 0.02 s (Goold & Jones 1995). The amplitude of these clicks also appears to decline rapidly, with clicks at the end of the creak more than 20 dB lower in level than the regular clicks (see figure 2; Madsen et al 2002b).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Clicks during creaks have an initial inter-click interval of ca. 0.2 s, which decreases to 0.02 s (Goold & Jones 1995). The amplitude of these clicks also appears to decline rapidly, with clicks at the end of the creak more than 20 dB lower in level than the regular clicks (see figure 2; Madsen et al 2002b).…”
Section: Introductionmentioning
confidence: 97%
“…A clicking whale often pauses for several seconds following a creak before resuming regular clicking. Based upon the acoustic features of these click sequences, creaks appear to be analogous to the terminal buzzes produced by echolocating bats as they close on targets (Goold & Jones 1995;see fig. 8 in Griffin 1958).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done in order to isolate two dominant frequencies (Goold & Jones, 1995). The separation of the data in a low-and high frequency band followed the same protocol as the filtering in the preprocessing of the data.…”
Section: Gabor Function Classification Splitting the Frequency Bandmentioning
confidence: 99%
“…The first approach was motivated by the results of Goold & Jones (1995), who showed that clicks from a single click train can have fairly constant dominant frequencies in at least two different frequency bands. For a male sperm whale, these frequencies can be found around 500 Hz and 2000 Hz.…”
Section: Introductionmentioning
confidence: 99%